Pengaruh Kinerja Manajer Investasi Terhadap Return Reksadana Saham Syariah di Indonesia (Periode 2011-2015) - Siti Zulva Rafika; Nisful Laila (Universitas Airlangga, 2017)
This research aims to find out the influence of stock selection and market timing toward the return of Islamic mutual funds of stock in Indonesia. This study used seven samples of Islamic mutual funds of stock in Indonesia were obtained using purposive sampling. The stock selection and market timing were counted using Treynor Mazuy Model. The approach used in this study is quantitative approach using double regressions. In analyzing the data, the technique used is panel data regression analysis by using Eviews 8 software. The result of this study shows that in the partially test, the stock selection is proven to have significant influence toward the return of Islamic Mutual Funds of Stock in Indonesia, and the market timing also has significant influence toward the return of Islamic Mutual Funds of Stock. The simultaneously test shows that stock selection and market timing significantly influence the return of Islamic Mutual Funds of Stock.